Persepsi dan Minat Masyarakat Terhadap Konsumsi Susu - Anggraeni, Erika Dewi; Hidayat, Syarif Imam; Amir, Indra Tjahaja (Jurnal Social Economic of Agriculture, 2021)
Indonesia has great potential in the development of the agribusiness sector. One of the sectors that can be developed is the livestock sector. Milk is one of the livestock products that are consumed daily by the community. In 2019, Indonesia's milk consumption was recorded at 16.23 liters/capita/year. Indonesia's milk consumption is still relatively low compared to Singapore and Malaysia. This study aims to determine public perception of milk and milk consumption, and public interest in milk consumption. Data were obtained from interviews through questionnaires and analyzed using descriptive analysis. The results showed that 65.6% of respondents chose a positive view of milk, 57.43% of respondents had a positive view of milk consumption and 74.16% of respondents had a positive opinion of the benefits of milk. There are 40% of respondents who have a moderate purchase frequency, 73.3% of respondents have a low consumption frequency and 61.7% of respondents have a low milk consumption measure.Keywords: Milk, Public Perception, Public Interest, Reason